Group dynamics : collectives of the modernist period - Mühling, Matthias; Althaus, Karin; Böller, Susanne; Henn, Sarah Louisa; Huttenlauch, Eva; Weber, Stephanie (Ostfildern : Hatje Cantz, 2022)
Nsukka School ; Grupo Dos Cinco ; Bombay Progressive Artists' Group & Lahore Art Circle ; Madrasat Al-Khartoum / Al-Kristaliyyun ; Grupa "A.R." ; Wuming Huahui / No Name Group ; Artistas del Pueblo & Martin Fierro ; Casablanca School ; Kokuga Sosaku Kyokai, Kokuyokai, Action, Mavo, Sanka
boek
Keywords: Art, Modern -- 20th century -- Exhibitions